2015
DOI: 10.3390/s150305687
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Reversal and Magnetic Anisotropy in Ordered CoNiP Nanowire Arrays: Effects of Wire Diameter

Abstract: Ordered CoNiP nanowires with the same length of 4 µm and varying diameters (d = 100 nm–600 nm) were fabricated by electrodeposition of CoNiP onto polycarbonate templates. X-ray diffraction, scanning electron microscopy, and high-resolution transmission electron microscopy confirmed the quality of the fabricated nanowires. Magnetic measurements and theoretical analysis revealed that the magnetization reversal and magnetic anisotropy were significantly influenced by varying of the diameters of the nanowires. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…3, it can also be seen that the H C , as well as the M r /M s , decreases with increasing l. We also observed that the H C and M r /M S were significantly influenced by varying the d of the nanowire. Similar results have been reported in multisegment nanowires such as CoNiP [36], Ni/Cu [37], NiCu/Cu [39], Co/Ni [40], Co/Fe [41], and Ni/Fe [42].…”
Section: The Influence Of the Geometrical Parameters On The Hysteresisupporting
confidence: 87%
See 1 more Smart Citation
“…3, it can also be seen that the H C , as well as the M r /M s , decreases with increasing l. We also observed that the H C and M r /M S were significantly influenced by varying the d of the nanowire. Similar results have been reported in multisegment nanowires such as CoNiP [36], Ni/Cu [37], NiCu/Cu [39], Co/Ni [40], Co/Fe [41], and Ni/Fe [42].…”
Section: The Influence Of the Geometrical Parameters On The Hysteresisupporting
confidence: 87%
“…Because MNs show novel and interesting properties with a specific structure, they have been studied to investigate the dependence of geometrical parameters such as the wire diameter [36][37][38], segment thicknesses [28,[37][38][39][40][41][42], and aspect ratio [43,44] on the magnetic properties. Moreover, the hysteresis properties of the Ising-type multisegment nanowire with alternating magnetic spin-1/2 and spin-1 segments were investigated by using the EFT with correlations.…”
Section: Introductionmentioning
confidence: 99%
“…When both components are magnetic, the saturation magnetization range will be limited to the minimum and maximum saturation magnetization of the components, except iron–cobalt MNWs with a 2:1 atomic ratio that leads to higher saturation magnetization [ 63 , 67 , 68 ], as shown in Figure 3 f. Generally speaking, having both magnetic components does not provide much flexibility to tailor the saturation magnetization as the encoding parameters. This is also valid when the MNWs are made of three components, such as iron, nickel, and cobalt, as trinary [ 69 , 70 , 71 ]. However, these cases are very useful to tailor other magnetic properties, such as coercivity, where, as an example, Permalloy (iron–nickel with a 1:4 atomic ratio) is one of the most popular compositions [ 61 , 67 , 72 , 73 ].…”
Section: Why Magnetic Nanowires For Nanobarcodes?mentioning
confidence: 99%
“…Metallic, magnetic, and semiconducting nanowires (NWs) are, nowadays, the focus of a great deal of attention among scientists coming from different research fields, due to the peculiar physico-chemical features exhibited by these materials with nanometer-sized dimensions and specific tailored geometries. Therefore, wire-shaped nanomaterials have become key elements in many modern technological approaches, including high-density magnetic data storage, energy conversion and harvesting, catalysis, sensing, photonics, and many others, where the size and shape of the nanoelements become essential to determine the unique magnetoelectronic properties exhibited by these systems [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%